13 Quantifying the Intensity of Adverse Events in Children Receiving Ibuprofen and Oxycodone Following Acute Fracture. (21st October 2022) - Gourlay, Katie; Ali, Samina
Abstract: Background: Treatment of pain is an essential component of optimizing an injured child's quality of life and experience. Ibuprofen and oxycodone are widely used for treating childhood fracture pain. While oxycodone is generally associated with increased frequency of adverse events (AEs), little is known on the comparative intensity of AEs associated with these medications. Objectives: Our primary objective was to quantify the frequency and intensity of AE's associated with ibuprofen and oxycodone in children following acute fracture. Our secondary objective was to assess functional outcome impairment in children taking ibuprofen and oxycodone, specifically their ability to eat, sleep, play, and attend school. Design/Methods: Patients aged 4-16 years diagnosed with a fracture in the Stollery emergency department who were prescribed either ibuprofen or oxycodone were recruited from 2010-2014. Patient characteristics were collected using a structured chart review. Families were called for the first three days after discharge and asked to report the frequency and intensity of AEs, as well as whether their child's ability to eat, sleep, play or attend school was impaired. Results: A total of 240 children were recruited (ibuprofen n=176, oxycodone n=59). Children using oxycodone were more likely to report any AE (p<0.001), nausea (p<0.001), vomiting (p<0.001), drowsiness (p<0.001), constipation (p=0.003), and dizziness (p<0.001), compared to ibuprofen. Using an 11-point rating scale, children receiving oxycodone reported more severe abdominal pain (oxycodone: mean 5.4 SD 3.1; ibuprofen mean 2.5 SD 1.4) on Day 1 (p=0.02) and worse constipation (oxycodone: mean 4.9 SD 2.1; ibuprofen mean 3.2 SD 2.2) over all three days (p=0.04). Children with upper limb fractures experienced more impairment in playing (oxycodone 93.8%, ibuprofen 65.7%, p<0.001) and attending school (oxycodone 80.9%, ibuprofen 57.6%, p=0.004) when prescribed oxycodone, while children with lower limb fractures experienced similar impairments regardless of medication used. Conclusion: Oxycodone is associated with more frequent overall, gastrointestinal, and neurologic AEs and higher intensity gastrointestinal AEs compared to ibuprofen. Function with upper limb fractures is worse in children prescribed oxycodone, over ibuprofen. Clinicians should be aware of differences in AE profiles when caring for children in pain.